(untitled) (Journal of the College of Languages (JCL), 2009)
Schemata are the underlying connections that allow new experience and information to be aligned with previous knowledge. When one reads a text he usually uses all his levels of schemata. Schemata enable us to make sense of what is perceived and experienced in the world. In poetry, readers usually examine carefully and deeply what they are reading in comparison with other sorts of discourse. Coherence is achieved when a reader perceives connections among schemata. It is a connection between linguistic and textual features of the text, and reader’s mental expectations as well as stored knowledge of the world. This paper discusses the role of schematic correlation in poetry, and the effect of different schematic background and difference among readers on schema change and interpretation of meaning.